2015
DOI: 10.1039/c5lc00552c
|View full text |Cite
|
Sign up to set email alerts
|

On-chip lysis of mammalian cells through a handheld corona device

Abstract: On-chip lysis is required in many lab-on-chip applications involving cell studies. In these applications, the complete disruption of the cellular membrane and a high lysis yield is essential. Here, we present a novel approach to lyse cells on-chip through the application of electric discharges from a corona handheld device. The method only requires a microfluidic chip and a low-cost corona device. We demonstrate the effective lysis of BHK and eGFP HCT 116 cells in the sub-second time range using an embedded mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Escobedo et al [ 90 ] showed electrical lysis of cells inside a microfluidic chip using a hand held corona device. They were able to lyse baby hamster kidney cells (BHK), enhanced green fluorescent protein human-CP cells (eGFP HCP) 116 and non-adherent K562 leukemia cells completely inside a microfluidic channel.…”
Section: Microfabricated Platforms For Cell Lysismentioning
confidence: 99%
See 1 more Smart Citation
“…Escobedo et al [ 90 ] showed electrical lysis of cells inside a microfluidic chip using a hand held corona device. They were able to lyse baby hamster kidney cells (BHK), enhanced green fluorescent protein human-CP cells (eGFP HCP) 116 and non-adherent K562 leukemia cells completely inside a microfluidic channel.…”
Section: Microfabricated Platforms For Cell Lysismentioning
confidence: 99%
“…Cells were lysed using a hand held corona device by applying electric field at the inlet of the device; ( b ) bright field and fluorescent images of before and after of lysis of K562 cells. Reproduced with permission from [ 90 ].…”
Section: Figurementioning
confidence: 99%
“…The theories behind corona discharge in liquids are diverse. Escobedo et al [ 61 ] used a handheld corona device, as shown in Figure 4 B (electric discharge of 10 to 30 kV: 300 ms), to lyse baby hamster kidney cells (BHK), enhanced green fluorescent protein human-CP cells (eGFP HCP) with an embedded microelectrode, and non-adherent K562 leukemia cells without microelectrodes.…”
Section: Lysis Techniquesmentioning
confidence: 99%
“…( B ) Schematic of the experimental setup using corona discharge. Reproduced from [ 61 ] with permission of The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…Bag et al [11] developed an improved method for the extraction of community DNA from different environmental and human origin samples by a combination of physical, chemical, and mechanical lysis methods for proper lysis of microbial DNA. A novel approach to lyse cells on-chip through the application of electric discharges can be used in plasmid recovery [12]. The combined action of enzymes, detergents, and high temperatures constitutes an interesting alternative for the large-scale disruption of E. coli cells and plasmid release [13].…”
Section: Introductionmentioning
confidence: 99%